A broadband piezo-electromagnetic hybrid energy harvester under combined vortex-induced and base excitations. (15th May 2022) - Hou, Chengwei; Li, Chunhui; Shan, Xiaobiao; Yang, Chongqiu; Song, Rujun; Xie, Tao
Highlights: A broadband hybrid energy harvester under wind and base excitations is proposed. Dual incentives significantly improve the output performance of the energy harvester. Magnet distance can alter the interaction strengtht and performance of the harvester. The peak power and frequency band can have 1242.86% and 400% increase respestively. Abstract: Wind energy harvesting is a green and advanced technology to persistently prop up low-power devices employed in wireless applications. For enhancing the capacity of vortex-induced vibration energy harvester, a broadband piezo-electromagnetic hybrid energy harvester is proposed. The harvester consists of two working units, a piezoelectric unit, and an electromagnetic unit, to concurrently scavenge the vortex-induced and base excitation vibration energy. And magnetic force is the main factor for connecting the two units. The harvester is studied by the methods of theoretical analysis and experimental measurement. Through comparing the experimental results and theoretical analysis, the accuracy of theoretical modeling is proved. And the output characteristic comparisons between the two separate excitations are presented through the theoretical method. Under the combined excitation of vortex-induced and base excitations, the harvester can obtain 1242.86% higher output power and 400% wider operating band compared with the single vortex-induced vibration. The performances of the proposed wind energy harvester under concurrent base and vortex-induced excitations are significantly greater than those based on the single excitation, which provides a good prospect for further exploring the energy harvesting system with multiple excitation sources.